La question animale dans l’entre-deux-guerres : renouveau iconographique et mutation axiologique dans Gédéon (1923-1939) - Laurence Olivier-Messonnier (Strenae)
Benjamin Rabier created an animal-themed comic in reviving his character Gédéon, a duck distinguished among the barnyard by his long neck, as well as by his intelligence, used in the pursuit of justice. The sixteen Gédéon picture books published between 1923 and 1939 offered a new approach in considering the animal world, which was unique for its time, and gave a second life to an obsolete production. This study brings to light the iconotextual originality of the Gédéon saga. Contextualization and cotextualization of the picture books is essential in analyzing the innovative factors found equally in the storyline and the illustration style. The animal question in children's literature in the interwar period is crucial, as it reveals a metamorphosis of anthropomorphism and raises the issue of an animal’s status.